2009
DOI: 10.1242/jeb.030338
|View full text |Cite
|
Sign up to set email alerts
|

Limits to sustained energy intake. XI. A test of the heat dissipation limitation hypothesis in lactating Brandt's voles (Lasiopodomys brandtii)

Abstract: SUMMARYThe maximum rate of sustained energy intake (SusEI) may limit reproductive effort, thermoregulatory capability and other aspects of an animal's energy expenditure. Consequently, factors that limit SusEI are of interest. The 'heat dissipation limitation hypothesis' suggests that maximum SusEI during lactation is limited by the capacity to dissipate body heat generated as a byproduct of processing food and producing milk. In the present study, we tested the heat dissipation limitation hypothesis in lactat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
74
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 75 publications
15
74
0
Order By: Relevance
“…Similar effects of decreased or increased temperature on lactation performance were observed in common vole (Microtus arvalis), Mongolian gerbil (Meriones unguiculatus) and Brandt's vole (Lasiopodomys brandtii, only in females with a litter size exceeding seven) (Wu et al, 2009;Simons et al, 2011;Yang et al, 2013). Contrary to the predictions of the HDL theory, however, females of European hares (Lepus europaeus) were able to reach their maximum energy turnover under thermoneutral conditions (Valencak et al, 2010) and lactating striped hamster (Cricetulus barabensis) females increased their food intake in the cold, but were not capable of producing more milk (Zhao, 2011).…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Similar effects of decreased or increased temperature on lactation performance were observed in common vole (Microtus arvalis), Mongolian gerbil (Meriones unguiculatus) and Brandt's vole (Lasiopodomys brandtii, only in females with a litter size exceeding seven) (Wu et al, 2009;Simons et al, 2011;Yang et al, 2013). Contrary to the predictions of the HDL theory, however, females of European hares (Lepus europaeus) were able to reach their maximum energy turnover under thermoneutral conditions (Valencak et al, 2010) and lactating striped hamster (Cricetulus barabensis) females increased their food intake in the cold, but were not capable of producing more milk (Zhao, 2011).…”
Section: Introductionmentioning
confidence: 59%
“…Rogowitz, 1998). Several experiments designed to resolve which of the two mechanisms limits females' energy budgets at peak lactation provided contradictory results (Hammond and Diamond, 1992;Speakman and McQueenie, 1996;Rogowitz, 1998;Hammond and Kristan, 2000;Johnson and Speakman, 2001;Johnson et al, 2001a,b;Wu et al, 2009;Duah et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this idea, dorsally shaved MF1 mice had increased thermal conductivity, and were thus able to produce more milk and wean heavier litters (Król et al, 2007). Studies on Brandt's voles (Wu et al, 2009) and Mongolian gerbils (Yang et al, 2013) both revealed that high temperatures (30°C) induced a reduction in milk production. Although these data supported the HDL theory, the effect in voles was greatest in females raising the largest litters, and in small litters there was no significant effect of high temperature (Wu et al, 2009).…”
Section: Introductionmentioning
confidence: 78%
“…The factors that limit the intake of food at peak lactation, and hence overall reproductive performance, have been the subject of repeated experimentation (Peterson et al, 1990;Hammond and Diamond, 1992;Weiner, 1992;Hammond et al, 1994;Koteja, 1996a;Rogowitz, 1998;Hammond and Kristan, 2000;Johnson et al, 2001a;Bacigalupe and Bozinovic, 2002;Król and Speakman, 2003a;Król and Speakman, 2003b;Zhang and Wang, 2007;Zhang and Wang, 2008;Wu et al, 2009;Zhao and Cao, 2009;Speakman and Król, 2011;Zhao, 2011;Zhao, 2012). Among several others, two factors that have emerged from this work appear to be significant: (i) the capacity of the mammary glands to produce milk and (ii) the capacity of the female to dissipate body heat (Peterson et al, 1990;Hammond and Diamond, 1992;Weiner, 1992;Hammond et al, 1994;Koteja, 1996a;Rogowitz, 1998;Hammond and Kristan, 2000;Johnson et al, 2001a;Bacigalupe and Bozinovic, 2002;Król and Speakman, 2003a;Król and Speakman, 2003b;Speakman and Król, 2005;Speakman and Król, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation